2008
DOI: 10.1111/j.1440-6055.2008.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse cuticular hydrocarbons from Australian canebeetles (Coleoptera: Scarabaeidae)

Abstract: Cuticular hydrocarbon components in beetles of six Australian melolonthines whose larvae damage sugarcane, Antitrogus parvulus (Britton), A. consanguineus (Blackburn), Lepidiota negatoria (Blackburn), L. picticollis (Lea), L. noxia (Britton) and Dermolepida alborhirtum (Arrow), are identified and compared. These species demonstrate species-specific cuticular hydrocarbon profiles with a number of unprecedented structures. Major components have been identified as polymethylated hydrocarbons, 3-methyl substituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…The present study shows that the 12 studied species of dung beetle have distinct chemical profiles of CCs, and their use as systematic characters has demonstrated to be very useful to distinguish genera and species in this specific group of Coleoptera. These CCs are similar to those observed in other groups of insects ( Gongyin et al 2007 , Fletcher et al 2008 , Baracchi et al 2009 ). Our results demonstrated that the cuticular hydrocarbon profile of 7 of the 12 dung beetle species included in this study (namely, B. gallicus , G. spiniger , J. nitidus , Ty.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study shows that the 12 studied species of dung beetle have distinct chemical profiles of CCs, and their use as systematic characters has demonstrated to be very useful to distinguish genera and species in this specific group of Coleoptera. These CCs are similar to those observed in other groups of insects ( Gongyin et al 2007 , Fletcher et al 2008 , Baracchi et al 2009 ). Our results demonstrated that the cuticular hydrocarbon profile of 7 of the 12 dung beetle species included in this study (namely, B. gallicus , G. spiniger , J. nitidus , Ty.…”
Section: Discussionsupporting
confidence: 89%
“… Jacob and Hanssen (1986) published one of the first studies demonstrating the use of CCs as taxonomic characters for the chemotaxonomy in Coleoptera. Since then, various studies on Coleoptera families showed that these cuticular characters were species specific within a family, such as in Tenebrionidae ( Lockey 1992 ), Curculionidae ( Page et al 1997 , Howard and Perez-Lachaud 2002 ), Staphylinidae ( Lusebrink et al 2007 ), and Scarabaeidae ( Fletcher et al 2008 ).…”
mentioning
confidence: 99%
“…Chemotaxonomy within the field of entomology has been around for many years, and it is widely accepted that CHC analysis provides an excellent means of species identification across a broad range of insect orders like Hymenoptera [15,[23][24][25][26][27][28][29][30][31][32], Isoptera [14,33], Blattodea [31,34,35] and Coleoptera [28][29][30]. CHC analysis has also been used for Diptera [7,22,31,[36][37][38][39], providing a complementary technique when the taxonomical identification is ambiguous or even not feasible, which could be due to the damaged physical condition or DNA degradation, or quite simply because the morphology between particular species is too similar to identify them [22,40].…”
Section: Discussionmentioning
confidence: 99%
“…Cuticular hydrocarbons (CHC) as a means of species identification has been studied for decades and is used to discriminate between different insect taxa [ 14 , 15 ]. Their epicuticular wax layer is consisting of hydrocarbons, fatty acids, alcohols, waxes, glycerides, phospholipids and glycolipids.…”
Section: Introductionmentioning
confidence: 99%
“…Peak identifications should be considered hypotheses and although they are consistent with published data, it was not the focus of this paper to conduct exhaustive identification of compounds. Prediction of peak identities were made by comparing RIs and diagnostic ions to the MS data of identified CHCs in other studies and the NIST14 (National Institute of Standards & Technology, Gaithersburg, MD, USA) library database [34][35][36][37][38]. Double bond locations were not identified.…”
Section: Chc Characterization and Identificationmentioning
confidence: 99%